2020
DOI: 10.1080/15230430.2020.1750805
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution remote sensing models for landscape-scale CO₂ exchange in the Canadian Arctic

Abstract: Climate warming is affecting terrestrial ecosystems in the Canadian Arctic, potentially altering the carbon balance of the landscape and contributing additional CO 2 to the atmosphere. High spatial resolution remote sensing data can enhance models of net ecosystem exchange (NEE) and its component fluxes, gross ecosystem exchange (GEE), and ecosystem respiration (ER) by quantifying vegetation structure and function over time. In this study, we explored the variability of daytime CO 2 exchange rates for three ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Though additional images within the growing season would likely add more nuance and clarity to the maximum NDVI (potentially by vegetation type), given that the growing season in the High Arctic is short and often cloudy, the lack of any trend in NDVI by day of acquisition within the growing season suggests that a single high spatial resolution optical data can be used with some level of confidence in a time series analysis. Similarly, Atkinson et al (2020) found that NDVI derived from a single peak growing season IKONOS image could successfully model CO 2 exchange rates at landscape scales for the CBAWO.…”
Section: Potential Influence Of Image Acquisition Dates On Ndvi Trendsmentioning
confidence: 83%
See 1 more Smart Citation
“…Though additional images within the growing season would likely add more nuance and clarity to the maximum NDVI (potentially by vegetation type), given that the growing season in the High Arctic is short and often cloudy, the lack of any trend in NDVI by day of acquisition within the growing season suggests that a single high spatial resolution optical data can be used with some level of confidence in a time series analysis. Similarly, Atkinson et al (2020) found that NDVI derived from a single peak growing season IKONOS image could successfully model CO 2 exchange rates at landscape scales for the CBAWO.…”
Section: Potential Influence Of Image Acquisition Dates On Ndvi Trendsmentioning
confidence: 83%
“…Additionally, the scar zones have been shown to have different ecosystem exchange and respiration rates than the surrounding undisturbed areas (Beamish et al 2014). As permafrost disturbances become more widespread in the High Arctic, tracking them, regardless of size, may help inform carbon sequestration and release models (e.g., Atkinson et al 2020).…”
Section: Active Layer Detachmentsmentioning
confidence: 99%
“…Atkinson et al. (2020) also found satellite‐derived NDVI (at a 4 m resolution) was able to explain spatial differences in the CBAWO daytime summer NEE and its component fluxes, GPP and R eco . In that study, fluxes were measured using static chambers across multiple vegetation communities, including less productive dry and mesic tundra where NDVI varied from approximately 0.05 to 0.25.…”
Section: Discussionmentioning
confidence: 95%
“…These successful relationships between satellite‐derived NDVI and CO 2 exchange processes at CBAWO likely reflect multiple factors that influence vegetation productivity. Across the CBAWO, spatial patterns in vegetation are organized along a seasonal moisture gradient (Atkinson et al., 2020) as they are in many other High and Low Arctic landscapes (Emmerton et al., 2016; Sjögersten et al., 2006; Walker et al., 2005). Soil moisture could influence interannual patterns in NEE as well and at the CBAWO, summer net CO 2 uptake significantly increased with precipitation.…”
Section: Discussionmentioning
confidence: 99%